Hybrid Modulation Scheme for CLLC Resonant Converter with Ultra-Wide Voltage Range for V2G Applications - Yang, Xiaotian; Wunder, Bernd; Yin, Shi; Schwanninger, Raffael; März, Martin; Lorentz, Vincent (2024 IEEE 6th International Conference on Direct Current Microgrids, ICDCM 2024, 2024)
In this paper, a hybrid modulation scheme consisting of phase-shift modulation (PSM) and pulse-frequency modulation (PFM) for a CLLC resonant converter for vehicle charging applications in DC Microgrids is proposed. To increase the operating range of the converter, an iterative design process of the converter is introduced. PSM, as a conventional alternative to PFM, can be used to further increase the operating range and improve the efficiency at light-load conditions. Since the converter in vehicle-to-grid (V2G) applications oftentimes operates under light-load conditions, implementing this hybrid modulation scheme can increase the efficiency dramatically. A novel idea of mode switching is also proposed in the paper to ensure smooth mode transitions. The working principle of this modulation scheme and the efficiency analysis were investigated in PLECS.
CRIS-Team Scopus Importer:2024-10-11
Keywords: CLLC; DC Charging; DC Microgrids; Efficiency Improvement; Hybrid Modulation; Mode Switching; V2G